"You Can't Always Get What You Want": A Novel Research Paradigm to Explore the Relationship between Multiple Intentions and Behaviours. Issue 2 (27th May 2016) - Sniehotta, Falko F.; Presseau, Justin; Allan, Julia; Araújo‐Soares, Vera
Abstract : Objective: Research investigating cognitive moderators of the intention–behaviour relationship and psychological consequences of failure to enact intentions is usually conducted in a single‐behaviour paradigm. A multiple‐behaviour paradigm is introduced which overcomes bias inherent to single‐behaviour designs and allows testing of novel hypotheses. Two exploratory studies illustrate the utility of this new paradigm by investigating the role of cognitive predictors and psychological correlates of intention–behaviour relationships. Method: The proposed method involves measuring multiple intentions across common areas of life activity at baseline and corresponding behaviours at follow‐up. In two studies, 51 intentions and behaviours were assessed (49 by self‐report, 2 objectively). In Study 1, participants ( n = 126) also completed self‐reported measures of everyday cognitive failures and dysexecutive behaviours, crystallised intelligence (Mill Hill Vocabulary Scale) at baseline and Quality of Life (QoL; follow‐up). In Study 2, objective executive function measures (Stroop, Go/NoGo task and Word Fluency test) were completed by N = 30 participants. Results: The total number of intentions, cognitive, and QoL measures were unrelated to the percentage of intentions enacted. Crystallised intelligence was related to successful intention implementation and problems with emotion regulation were associated with forming fewer intentions and with fewer failed intentions. QoL was strongly related with more intentions, regardless of whether or not these were implemented. Study 2 showed that cognitive flexibility (word fluency) and task errors, rather than Stroop effect and Go/No‐Go performance were related, to intention–behaviour congruence. Conclusion: Intention–behaviour relationships might be better understood when considering the multiple intentions and behaviours that people are engaged in at once at any one point in time. A multiple‐behaviour paradigm suggests novel hypotheses. Preliminary findings reported here require replication. Anticipated applications of the paradigm are outlined and discussed.